A Study of Gender Equality and Caste Issues As Reflected in Works of Meena Kandasamy: Exploring Gender Equality and Caste Issues in the Works of Meena Kandasamy (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Caste and Gender equality literature is totally weaved around Dalit community and their life experiences, especially of the people who belong to the lower strata of the society. There is a real character that is underlying behind the hypothetical character that is explained in the story. This story is based on the real story that will unveil about the reach incidents happening around the society and in every genre of Dalit literature. The literariness and fictionalization be it related to poetry or prose is totally based on the real incidents and situations. An emerging poet, fiction writer, translator, journalist and a social activist, Meena Kandasamy maintains her focus, in throughout her writing, on caste annihilation and the issue of woman‟s equality on par with a man. She is hailed as the first Indian woman poet writing Dalit poetry in English.Dalit literature is a resistance kind of literature. It is very important for a woman to address (or) present the issues that are experienced by the women in the society. It is also important to encourage writers, especially women writers from the marginalized class to have a place in literature. The society is dominated by males in every level. There are many male writers belonging to marginalized class are accused of not giving equal opportunity for women Dalit writers to present their works. The present research paper has evaluated the gender equality and caste issues as reflected in the works of Meena Kandaswamy.